Konsep Diri dan Disposisi Matematis: Bagaimana Hubungan Terhadap Hasil Belajar Siswa Sekolah Dasar? - Fridolin Vrosansen Borolla; Sumarah Suryaningrum; Hediaty La Sitiman (STKIP Taman Siswa Bima, 2023)
The research objective was to determine the relationship between self-concept and learning outcomes, determine the relationship between mathematical dispositions and learning outcomes, and determine the relationship between self-concept and mathematical disposition on learning outcomes. The study used a survey method with correlation techniques for fourth-grade students. The results showed that 1) there was a positive relationship between self-concept and learning outcomes; 2) there is a positive relationship between mathematical dispositions and student learning outcomes, and 3) there is a positive relationship between self-concept and mathematical dispositions on learning outcomes. Thus, the study results can be concluded that the learning outcomes of elementary school students have a positive relationship between self-concept and mathematical disposition